叉流板式间接蒸发冷却换热器的实验研究 - 赵振生; 任承钦; 涂敏; 曾阳; 王华辉 (Zhileng xuebao)
An experimental investigation was conducted on the performance of a crossflow plate type heat exchanger used as an indirect evaporative cooler.It is found that both the air mass flow rate and the ratio of the mass flow rate have a significant effect on the heat exchanger performance.The clear difference in performance is found for dry and wet conditions due to the great change in the ratio of the heat capacity rate of the two fluids.The experimental results show that the actual friction factor was greater t...